Demonstration Method Better Increased Knowledge, Attitude, and Skills on Hand Washing With Soap in Elementary School Students - Polly, Junitry Yublina; Nayoan, Christina R; Limbu, Ribka; Marni, Marni (Journal of Public Health for Tropical and Coastal Region, 2024)
Background: Every year, about 100,000 children in Indonesia die from diarrhea. In 2021, diarrhea cases in Taurus Health Center, Kupang, East Nusa Tenggara working area occurred more in elementary school children. Hand washing with soap (HWS) reduced diarrhea rates by 47%. This study aimed to analyze the different effect between lecture and demonstration methods on knowledge, attitudes and skills on hand washing with soap in GMIT Manumuti Elementary School students.Method: This quasi-experimental study was done in “pretest-posttest group design”. The subjects were all of 68 students in grade 5 (total sampling technique), who were evenly and randomly divided into 2 groups of lecture and demonstration. Data were collected through observations and interviews using structured questionnaires and were analyzed by paired and independent sample t-tests.Results: The subjects were 10-12 years old and 58.5% were boys. The mean knowledge scores increased from 52.2±8.89 to 75.1±7.17 (p=0.001) in the lecture group and from 62.5±8.89 to 86.9±7.17 (p=0.001).in the demonstration group, respectively. The mean attitude scores increased from 57.9±10.52.to 70.1±5.46 (p=0.001) in the lecture group and from 67.1 ±10.11 to 82.8±8.78 (p=0.001) in the demonstration group, respectively. The mean skill scores increased from 53.3±13.38 to 68.94±7.80 (p=0.001) in the lecture and from 60.76±17.11 to 82.7±10.33 (p=0.001) in the demonstration group. The mean knowledge, attitude and skills’ scores in the demonstration group after the intervention were all higher (p<0.05) than the control group.Conclusion: Demonstration method increased knowledge, attitude and skills on hand washing with soap better than the lecture method in elementary school students at GMIT Manumuti Elementary School.